Design of a toolkit for real-time executive function assessment in custom-made virtual experiences and interventions. Issue 158 (February 2022) - Williams, Rua M.; Alikhademi, Kiana; Gilbert, Juan E.
Highlights: Toolkit for real-time assessment of executive function in custom Virtual Reality experiences with measurements that directly compare to traditional clinical measures. Verification of replication of traditional executive function tasks in VR. Exploration of custom executive function tasks in VR, regardless of task complexity. Abstract: Virtual Reality (VR) and other game-like experiences are popular intervention platforms in neurocognitive rehabilitation research. Executive Functions (EF), the cognitive processes that regulate attention and goal-oriented action, are recognized as a domain of concern in several congenital and acquired neurocognitive conditions (e.g.: ADHD, autism, addiction, cognitive decline, traumatic brain injury, and stroke). VR-based simulations of real-world tasks have shown potential for rehabilitation in independent functioning. The custom nature of such projects makes cross-intervention analysis difficult and complicates development of best-practices. We have designed a toolkit for building virtual interactions that can consistently replicate traditional cognitive tests (such as the Wisconsin Card Sorting Task and Multitasking Task) as well as extend to more complex tasks in any virtual context. Analysis of participant performance data between traditional tasks and these VR replications may indicate the toolkit can successfully replicate traditional measures while also extending into more complex contexts.